STUDY OF THE KINEMATICS OF MOTION OF STATIC BALANCED SPECIAL TURNING DEVICES IN THE PROCESS OF THEIR DESIGN IN SOLIDWORKS - HOROKHOVSKYI, VIKTOR; HORDIEIEV, ANATOLII; KOSTYUK, NAZAR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper considers the issue of engineering analysis of technical systems using computer modeling, in particular, improving the process of static balancing of special turning devices during their design using the SOLIDWORKS engineering analysis system, which allows conducting numerical experiments to determine their characteristics, namely mass, coordinates of the center of gravity for the purpose of further static balancing of special turning devices during their design. The paper analyzes the capabilities of various software products for solving the scientific and technical problem of static balancing during the design process and determining the critical speeds of motion of complex multi-mass and multi-body systems and justifies the choice of the modern SOLIDWORKS software product. A methodology for computer modeling in SOLIDWORKS is proposed for solving problems of static balancing of multi-mass and multi-body systems during their design process with subsequent verification of the correctness of the calculations of the location of the coordinates of the center of gravity of a complex system after static balancing. The proposed method of static balancing of special turning devices in the process of their design with determination of the mass of the counterweight and its location provides accurate determination of the center of gravity of the machine tool device and the coordinates of its location at the design stage and reduces experimental studies of static balancing after the manufacture of the machine tool device, which speeds up the time for its implementation in the technological process of processing workpieces. In further studies, it is proposed to conduct modeling and calculations of kinematic and dynamic parameters of complex multi-mass objects and compare them with the results of calculations using the recommended values ​​of the center of mass coordinates. The kinematics of motion of statically balanced special turning devices were studied and the critical machine speeds were determined. The range of cutting speeds for optimal process productivity was recommended.